(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research aims to prepare a criterion to assess the creative thinking skills of the students of Art Education Department- Stage four in the subject of Project- field of drawing at the College of Basic Education in Sulaimani University, aiming at being beneficial to the lecturers and evaluation committees of students’ products in the field of drawing. Based on the type and nature of the research, a descriptive method is applied. Since no general or specific criterion does exist in the evaluation of the projects, thus the researcher resorted to the general and specific objectives of Project subject. From this perspective, a criterion in a form of creative skills and general principles of drafting and criticism is established. Moreover, identification of creative skills from previous studies and resources in the field of art education, psychology of creativity, and art is set, including preparing (29) educational objectives which were primarily handed out through surveys to the experts in the field of education, Art, and measurement and evaluation, following receiving the opinions and suggestions addressed by the experts, changes were made in (9) of the objectives, (20) objectives were pointed to the criterion. In order to stabilize the criterion, it was applied to the initial samples of the same project in Art Education Department.The correlation value between the levels was also found by the Person correlation coefficient with a value between (0.20-0.50)